“Comply or explain” in the EU, or the new human rights reporting obligation: an analysis of directive 2014/95/EU - Fernández Gaztea, Joseba; Muñoz Fernández, Alberto (CUADERNOS DE DERECHO TRANSNACIONAL, 2017)
Abstract: This article aims to offer an interdisciplinary perspective in regard to EU Directive 2014/95. It caters to the interests of development experts and legal experts. An analysis of the Directive constitutes a micro-view on the wider issue of business-human rights. The analysis provides a chance to reflect upon wider development implications. The first half of this article deals with the development character of the Directive and its connection to business-human rights narratives. The second half offers a legal analysis of its precepts. Keywords: disclosure, non-financial information, business and human rights, development, corporate social responsibility. El principio “cumplir o explicar” en la Unión Europea, o la nueva obligación de divulgar información sobre derechos humanos: un análisis de la Directiva 2014/95/UE Resumen: Este artículo ofrece una perspectiva multidisciplinar sobre la Directiva 2014/95/UE, de interés tanto para los juristas como para los especialistas en desarrollo. El análisis de la Directiva constituye un estudio sobre un aspecto concreto en el campo de los negocios y los derechos humanos. Además, pone de manifiesto las implicaciones que esta norma tiene en el ámbito del desarrollo. Esta cuestión se abordará en la primera parte del artículo, junto con contextualización de la Directiva dentro de las corrientes actuales en el sector de los negocios y los derechos humanos. La segunda parte ofrece un análisis del articulado de la norma. Palabras clave: divulgación, información no financiera, negocios y derechos humanos, desarrollo, responsabilidad social corporativa. doi: https://doi.org/10.20318/cdt.2017.3622